Applications of Point-of-Care Ultrasound (POCUS) in the Diagnosis and Management of Heart Failure: A recent literature review (Research, Society and Development, 2025)
Introduction: Heart Failure (HF) is one of the leading causes of emergency department visits, posing a significant clinical and economic impact. The diagnosis of decompensated HF remains challenging, particularly in patients with acute dyspnea, due to the limitations of physical examination, chest radiography, and isolated biomarkers. This article aims to critically review recent scientific evidence on the use of POCUS in HF, highlighting its diagnostic accuracy, prognostic value, clinical applicability, and limitations, based on studies published in the last five years and identified through a specific PubMed search.Methods: A qualitative narrative review was conducted using the PubMed database.Results and Discussion: The included studies demonstrate that POCUS presents high diagnostic accuracy for acute HF, especially when utilizing multi-organ approaches that integrate lung ultrasound, focused echocardiographic assessment, and venous analysis. Beyond diagnosis, POCUS showed prognostic utility by identifying residual subclinical congestion associated with a higher risk of hospital readmission. However, the literature emphasizes the need for an integrated interpretation of findings, considering the limitations of isolated parameters such as B-lines and inferior vena cava diameter. Additional evidence indicates the expansion of POCUS to alternative settings, such as hospital-at-home programs.Conclusion: POCUS is a valuable tool in the diagnosis, prognostic stratification, and management of heart failure, with the potential to optimize clinical decisions and outcomes. Its widespread incorporation depends on the standardization of protocols, structured training, and validation through additional prospective studies.